Analysis of Customer Perception in the Use of Micro Product Financing Using Murabahah Contract Case Study of BSI KCP Medan Adam Malik - Hayyah, Azka Wardatul; Nurlaila, Nurlaila (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze customer perceptions of the use of micro credit financing with a focus on the case study of Bank Syariah Indonesia (BSI) KCP Medan Adam Malik. Utilizing surveys and qualitative data analysis, the research methodology aims to understand the advantages and disadvantages of the sample through observation, interviews, and document analysis of the sample's perception of products using the Murabahah principle. In this context, the study examines the factors that influence public trust in the progress, transparency, and quality of the implementation of Murabahah law. The survey collected responses from BSI KCP Medan Adam Malik customers, while qualitative data analysis was conducted to identify customer views in more detail. The findings of this study are expected to help in understanding the effectiveness of the implementation of the Murabahah model in developing micro products and how it affects the needs and expectations of customers. The practical implications of this can help Islamic banks improve their products and services and strengthen their bonds with customers, especially at BSI KCP Medan Adam Malik.